Evaluate please

Asked by vshrikanth | 6th Mar, 2010, 11:25: AM

Expert Answer:

x3 + y3 + z3 = 3xyz  if x + y + z = 0

Here,

x- a + x - b + x-c = 3x - (a+ b+ c)    

                            = 3x - 3x                 (Given)

                           = 0

(x-a)3+(x-b)3+(x-c)3 = 3 (x-a)(x-b)(x-c)

So, (x-a)3+(x-b)3+(x-c)3 - 3 (x-a)(x-b)(x-c) = 0

Answered by  | 6th Mar, 2010, 12:36: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.